2020
DOI: 10.3390/polym12020479
|View full text |Cite
|
Sign up to set email alerts
|

CD133 Targeted PVP/PMMA Microparticle Incorporating Levamisole for the Treatment of Ovarian Cancer

Abstract: Levamisole (LEVA) is used to treat worm infections, but it can also inhibit cancer cell growth by inhibiting the aldehyde dehydrogenase pathway. Therefore, here, we developed a drug carrier targeting CD133, a biomarker overexpressed in ovarian cancer cells. The particle structure and cytotoxicity of the prepared LEVA-containing particles—called LEVA/PVP/PMMA microparticles (MPs) (because it used matrix material polyvinylpyrrolidone (PVP) and poly(methylmethacrylate) (PMMA))—were investigated in the ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Moreover, it was suggested that levamisole mimics the function of nonsteroidal anti-inflammatory drugs and inhibits endothelial cell proliferation, migration, and tube formation [80] . Wang et al [81] evaluated the effect of levamisole on an ovarian cancer cell line. They observed that levamisole exhibited a substantial effect on decreasing the rate of proliferation and growth of ovarian cancer cells in a dose-dependent manner [81] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was suggested that levamisole mimics the function of nonsteroidal anti-inflammatory drugs and inhibits endothelial cell proliferation, migration, and tube formation [80] . Wang et al [81] evaluated the effect of levamisole on an ovarian cancer cell line. They observed that levamisole exhibited a substantial effect on decreasing the rate of proliferation and growth of ovarian cancer cells in a dose-dependent manner [81] .…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [81] evaluated the effect of levamisole on an ovarian cancer cell line. They observed that levamisole exhibited a substantial effect on decreasing the rate of proliferation and growth of ovarian cancer cells in a dose-dependent manner [81] . Concomitant use of levamisole with common anticancer drugs such as chlorambucil, leucovorin, and fluorouracil has been shown to be strongly synergistic, and as a result, researchers have recommended the concomitant use of levamisole with anticancer agents [82 , 83] .…”
Section: Resultsmentioning
confidence: 99%
“…Koppany Visnyei et al confirmed that emetine inhibited the proliferation of glioma cells 39 . Levamisole minimizes drug side effects and inhibits the activity of ovarian cancer cells 40 . Riboflavin has a blue light activation effect, which produce reactive oxygen species (ROS) to inhibit the activity of cancer cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…39 Levamisole minimizes drug side effects and inhibits the activity of ovarian cancer cells. 40 Riboflavin has a blue light activation effect, which produce reactive oxygen species (ROS) to inhibit the activity of cancer cells. 41 Some drugs have new therapeutic effects that allow them play an unexpected role in the treatment of certain diseases, which accelerates the process of drug development.…”
Section: Verification Of the Reliability Of Nup37 Analysis In Gliomamentioning
confidence: 99%
“…CD133 + is a glycosylated membrane protein that was initially discovered in murine neuroepithelial stem cells and is identified as a marker for CSCs in brain tumors (65). A study by Liou (65) revealed that CD133 can modulate cell cycle progression by affecting Wnt signaling and promoting the invasiveness of tumor cells (64)(65)(66)(67). CD117 is a tyrosine kinase receptor, and peritoneal fluid obtained from patients with OC having CD117 + cells can form tumors with the same self-renewal and differentiation capacity as cells derived from the tumor (68).…”
Section: Ocscs and Markersmentioning
confidence: 99%